Ḥarakah al-Ṭullāb wa al-Siyāsah: Dirāsat fi Mawqif al-Ṭullāb al-Muslimīn al-Indūnīsiyīn min al-Siyāsah bi Indūnīsīyā - Wildan, Muhammad (Studia Islamika, 2001)
Since the very beginning of Indonesian nationalism, students have been instrumental in Indonesian politics. The proto-nationalist student organization, Budi Utomo, established in 1908, was one of the central proponents of the nationalist movement at the turn of the century. Students also played a critical role in the political developments since 1965, when Orde Lama (Old Order) ended and the Orde Baru (New Order) began. The present article focuses on those students who were involved in the Muslim youth organization PII (Pelajar Islam Indonesia, Indonesian Muslim Students' Association), particularly on its dynamic political attitudes during the Old Order and New Order.DOI: 10.15408/sdi.v8i1.697